Nichole Coleman. The Right to Difference: Interculturality and Human Rights in Contemporary German Literature. University of Michigan Press, 2021. - Priscilla D Layne (Studies in 20th & 21st Century Literature, 2024)
Review of Nichole Coleman. The Right to Difference: Interculturality and Human Rights in Contemporary German Literature. University of Michigan Press, 2021. 270 pp.
Keywords: literature; universalism; interculturality; diversity; human rights